Infrastructure and growth: The Latin American Case - Elías, Víctor (Estudios de Economía, 2016)
The main objective of this paper is to evaluate the role of infrastructure investment (ISI) in the economic growth of Latin American countries. Previous studies evaluating the role of infrastructure capital on economic growth have generally focused on industrialized countries.